Antro-naso-choanal polyp (proposed name)/antrochoanal polyp (famous name): excision without recurrence by combined endoscopic approach - Khalefa, Khaled M. Mokbel; Ekiaby, Reham El; Mokbel, Hana Khaled (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
The primary goal of treatment for antro-naso-choanal polyp must be in the form of complete removal with total cleaning of the maxillary sinus to prevent recurrence. This retrospective case series study with (Institutional Review Board cod is R.25.08.3334), included 20 patients with antro-naso-choanal polyps (ANCP) (the proposed name for the usual name of the antrochoanal polyp). Patients were 14 males and 6 females with ages ranged from18-40 years. Under general anesthesia all cases were operated by combined transnasal and sublabial endoscopic approach. There was any recurrence through the average 18 months of follow up period. It is concluded that combined transnasal and sublabial endoscopic excision of antro-naso-choanal polyp is the best approach for complete removal without recurrence.